EARLY METABOLIC AND WEIGHT LOSS OUTCOMES IN LAPAROSCOPIC SLEEVE GASTRECTOMY PLUS PROXIMAL JEJUNAL BYPASS (SLEEVE PJB) - Gerard, Adrian; Velayutham, Rama Moorthy; Supramaniam, Kumaresan; Rajandran, Aravinthan; Rosli, Ahmad Farhan; Rahmahtullah, Ijaz bt Hallaj; Rahim, Anilah bt Abdul (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION Sleeve plus procedures are sleeve gastrectomy variations that include numerous procedures such as SADI-S (single anastomosis duodenoileal bypass with sleeve), loop duodenojejunal bypass with sleeve gastrectomy (Loop DJB) and sleeve gastrectomy plus proximal jejunal bypass (Sleeve PJB). We have performed Sleeve PJB for selected patients in our centre. METHODOLOGY We did a retrospective analysis of patients who underwent laparoscopic sleeve PJB in Hospital Raja Permaisuri Bainun Ipoh in 2023. We analysed demographics, weight, BMI and HbA1c. All patients had a sleeve gastrectomy utilizing our standard operative technique. For the proximal jejunal bypass (PJB), jejunum was transected at 50 cm distal to the ligament of Treitz. Subsequently, another 270 cm to 300 cm of jejunum was measured from the divided region and a side-to-side jejunojejunostomy was done. RESULT A total of 6 patients underwent this procedure. All patients were not amenable to gastric bypass and wanted a more durable surgery in terms of weight loss and metabolic outcomes. Four of them had pre-diabetes and two patients had diabetes based on HbA1c. Cumulative mean age, weight and BMI were 44 years, 109 kg and 44 kg/m2 respectively. The HbA1c for the prediabetes and diabetes group preoperatively were 6% and 8% respectively. Postoperatively at 6 months, the HbA1c was 5.4% and 5.9% respectively for each group. Cumulative postoperative mean current weight and mean percentage of total weight loss (%TWL) at 6 months were 91.5 kg and 20.57%. CONCLUSION This study shows that early outcomes for sleeve PJB are favourable and likely a non-inferior option for patients who are not amenable to a standard gastric bypass.